Impact of SARS-CoV-2 Preventive Measures against Healthcare-Associated Infections from Antibiotic-Resistant ESKAPEE Pathogens: A Two-Center, Natural Quasi-Experimental Study in Greece - Emmanouil Bolikas; Eirini Astrinaki; Evangelia Panagiotaki; Efsevia Vitsaxaki; Stamatina Saplamidou; Ioannis Drositis; Dimitra Stafylaki; Georgios Chamilos; Achilleas Gikas; Diamantis P. Kofteridis; Evangelos I. Kritsotakis (MDPI AG, 2023)
The COVID-19 pandemic led to unprecedented stress on healthcare systems worldwide, forming settings of concern for increasing antimicrobial resistance. We investigated the impact of SARS-CoV-2 preventive measures against healthcare-associated infections (HAIs) from antibiotic-resistant bacteria in two tertiary-care hospitals. We compared infection rates between March 2019 and February 2020 (pre-intervention period) and March 2020 and February 2021 (COVID-19 intervention period) from drug-resistant ESKAPEE bacteria (methicillin-resistant Staphylococcus aureus; vancomycin-resistant Enterococci; carbapenem-resistant Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter species and Escherichia coli). Over 24 months, 586 drug-resistant ESKAPEE HAIs occurred in 439 patients (0.3% of 179,629 inpatients) with a mean age of 63 years, with 43% being treated in intensive care units (ICUs), and having a 45% inpatient mortality rate. Interrupted time series analysis revealed increasing infection rates before the intervention that were sharply interrupted by abrupt drops for most pathogens and henceforth remained stable in the ICUs but progressively increased in ordinary wards. In the ICUs, the pooled infection rate was 44% lower over the intervention period compared to the pre-intervention period (incidence rate ratio (IRR) 0.56, 95%CI 0.41-0.75, p < 0.001). Pooled infection rates in the wards were slightly higher over the COVID-19 period (IRR 1.12, 95%CI 0.87-1.45, p = 0.368). The findings confirmed the ancillary beneficial impact of the enhanced bundle of transmission-based precautions adopted against SARS-CoV-2 in rapidly constraining antimicrobial-resistant HAIs in two Greek hospitals.